ANALISIS PENDAPATAN USAHATANI KAKAO SAMBUNG SAMPING DI DESA SIGIMPU KECAMATAN PALOLO KABUPATEN SIGI - Lusnita, Lusnita; Muis, Abdul; Tangkesalu, Dance (AGROTEKBIS, 2018)
This study aims to determine the characteristics of the cacao side grafting farmer in the Sigimpu village and analysisÂ  of the farmer income. This research was conducted in September to October 2016. The determination of respondents was calculated using a simple random sampling of 32 respondents. The results showed that Sigimpu farmers respondents have the characteristics that are: most farmers average men age are 44 years, the average level of formal education of 6 years (the base rate) is still low, the average number of family dependents is 3 people, the average cocoa farming experience is 20 years. The average income of cocoa side grafting farming in the Sigimpu village was Rp.23.457.187,50/1,28 or Rp.18.325.927,70/Ha, the total everage cost of the farming was Rp.3.905.955,06/1,28Ha or Rp.3.051.527.39/Ha and the everage income side grafting of the farmers is Rp. 19.551.232,40 /1,28 Ha atau Rp. 15.274.400,30 /Ha and average farming income each month is Rp. 4,994,391.32 / 1,43Ha / month or Rp. 3,457,616.30/ha/month.Â Key words : Farmer income, Side grafting cocoa.